Growth and production of dwarf coconut in saline-sodic soil under doses of potassium sulfate - Tiago de A. Pereira; Lauter S. Souto; Francisco V. da S. Sá; João A. Dutra Filho; Tarso M. A. de Souza; Emanoela P. de Paiva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective was to study the influence of potassium sulfate doses applied to the soil on the growth and production of green dwarf coconut (Cocos nucifera L.) grown in saline-sodic soil. The experiment was conducted from January 2013 to January 2016, in a commercial plantation in the Sector 7 of the ‘Várzeas de Sousa’ Irrigation District, PB, Brazil, in saline-sodic Ebanic Vertisol. The experiment used coconut plants belonging to green dwarf variety, arranged in a 7.0 x 7.0 m rectangular shape, starting the third year in the production stabilization stage. The adopted experimental design was randomized blocks, evaluating five doses of potassium sulfate (K2SO4) (0, 0.52, 1.04, 2.08 and 4.16 kg plant-1 year-1), with four replicates of four plants each, totaling 20 experimental units. The K2SO4 doses positively influenced the growth and production of green dwarf coconut trees in saline-sodic soil. The highest growth in height and diameter of this coconut variety was obtained at the K2SO4 dose of 4.16 kg plant-1 year-1. The largest fruits and water volume in the first year of production were obtained with K2SO4 doses from 2.08 to 2.81 kg plant-1 year-1.